Correlation Study of Enculturations Surah Ash Shaff: 10-11 with Spiritual Quotient A Case Study - Hutasuhut, Julianto; Saragih, Al Kausar (International Journal for Educational and Vocational Studies, 2020)
In an effort to create a national cultural agenda of "Towards a Superior Indonesia", the concept of human resources development should be reconstructed to lead to the new concept of focusing on the development of spiritual quotient (SQ). The main reason for this is that the concept of SQ is the highest human intelligence that enables IQ and EQ to function effectively. The purpose of this study was to find out the correlation of Surah Ash Shaff: 10-11 enculturation through memorizing and reading it at each commencement of the lecture with the spritual quotient of the student / student at Faculty of Economics, Universitas Muslim Nusantara Al-Washliyah. The type of research used is assosiaitive research with quantitative approach. The study population are students of the Faculty of Economics, Universitas Muslim Nusantara Al-Washliyah/sample and sample size was set 165 people with purposive sampling technique. The data collection tool used was a questionnaire using Likert scale measurement. The data analysis techniques used were validity test, reliability test, classical assumption test, correlation test and to test hypothesis using Pearson correlation test and Spearman's correlation test as well as the coefficient of deterioration test (R test). The results of the coefficient of determination (R test) concluded, the contribution of the Surah Ash Shaff: 10-11 enculturation was able to explain the spiritual quotient variable by 65.8% while the other contribution of 34.2% was influenced by the other variables.